P181 Adherence to Treatment in Patients with Bronchiectasis Infected with Pseudomonas Aeruginosa. (19th November 2012) - McCullough, A R; Hughes, CM; Tunney, M; Elborn, JS; Bradley, JM
Abstract : Introduction: Patients with bronchiectasis and P. aeruginosa infection are often prescribed a complex regimen of inhaled antibiotics, other respiratory medicines and airway clearance techniques (ACT). Current bronchiectasis guidelines recognise that adherence to treatment is important in this population but no published studies have determined the level of adherence to treatment in patients with bronchiectasis infected with P. aeruginosa. Aim: The aim of this study was to determine adherence rates to inhaled antibiotics, other respiratory medicines and ACT in patients with bronchiectasis infected with P. aeruginosa . Methods: Patients with bronchiectasis (confirmed by HRCT) were recruited from hospital respiratory clinics if they had a positive sputum culture for P. aeruginosa and were using inhaled antibiotics. Prescription refill data were used to calculate percentage adherence by dividing the amount collected by the amount prescribed, multiplied by 100. Participants were categorised as adherent (score≥80%) and non-adherent (score<80%) to inhaled antibiotics and other respiratory medicines using this method. Participants completed the modified Self-reported Medication-taking Scale for ACT (score 0–5; adherent score≥4, non-adherent score<4). Spirometry was performed according to ATS/ERS guidelines. Chi square tests were used for between group analyses. Results: 75 participants were recruited: 24M/51F; mean (SD) age 64 (8) yrs; FEV1 61 (25) % predicted. Sixty-four (85%) participants were prescribed colomycin, 11 (15%) were prescribed tobramycin, 68 (91%) were prescribed bronchodilators and 65 (87%) were prescribed inhaled corticosteroids. All participants were prescribed ACT; active cycle of breathing techniques (n=39, 53%) and Acapella® (n=45, 61%) were most commonly prescribed. Eleven percent (16%) participants were adherent to all treatments. Fifty-two percent and 51% of participants were adherent to inhaled antibiotics and other respiratory medicines, respectively. Thirty-nine percent of participants were adherent to ACT. Adherence category varied significantly between inhaled antibiotics and other respiratory medicines (p=0.04), with 34% of participants being adherent to one treatment and not the other. Conclusion: Patients with bronchiectasis patients infected with P. aeruginosa have a high burden of treatment. Only 11% of patients were adherent to all treatments, half were adherent to medicines and even fewer were adherent to ACT, indicating that patients make decisions about which treatments to use.